KAJIAN PERAN ANGKAK PADA KUALITAS TEMPE KEDELAI-LAMTORO GUNG (Leucaena leucocephala) - Rosida, Dedin F; HP, Sudaryati; Constantia, Fenny (UPN VETERAN JAWA TIMUR, 2012)
In general, people use soy as an ingredient of making tempeh, tempeh increased demand resulted in a growing number of imported soybeans.The efforted can be done to overcome this is by replacing or mixing of raw materials (soybeans) with other materials. Substitute one ingredient is soy beans lamtoro stage. Diversification of products tempeh can be done by adding lamtoro gung and red yeast rice in soy tempeh. This study aims to determine the effect of the proportion of soybean seeds: lamtoro gung and the addition of red yeast rice to quality tempe. Research using Complete Randomized Design (CRD) factorial pattern with two factors and two replications, the proportion of soybean Factor I: lamtoro gung 70%: 30%, 50%: 50%, 30%: 70%. Factor II, the addition of red yeast rice 1%, 2%, 3%. The results showed that the best treatment is the treatment the proportion of soybean: lamtoro gung (70:30) and the addition of 1% red yeast rice is produced tempeh with criteria 1% addition of red yeast rice that has a water content of 62.42%, ash content 3.30%, levels 14.99% protein, fat content of 3.99%, 3178.41 ppm phenol content, antioxidant activity of 59.47%, texture (hardness) 0.241 mm / sec and the gr 72 favorite color, flavor 75, flavor 73, compactness 71 .Key words: soybean, lamtoro gung red yeast rice